Penentuan Kriteria pada Pemilihan Supplier di Bidang Otomotif - Tarigan, Elsya Paskaria Loyda; Zetli, Sri; Prasetyo, Bahariandi Aji; Sumantika, Arsyad; Tambunan, Juniansyah (JURNAL REKAYASA SISTEM INDUSTRI, 2024)
Competition in the automotive world causes business people to look for ways to satisfy consumers. One way that can be done by business people is to choose the best supplier, who can meet consumer needs so that consumers feel satisfied. UKM YY is one of the businesses engaged in the automotive sector. Some problems in this UKM are related to the products offered by suppliers, namely: bad quality, late delivery, and irresponsibility for product, both in terms of quantity and quality. Some of these things cause business people to be reluctant to use the product again so that suppliers lose customers. This study aims to get best supplier, to fullfill consumer needs by using the AHP method. The criteria that most wanted of the business are quality and responsibility of the supplier. The supplier that choosen is Triwarna Color Center.